Evaluation of antioxidant, anxiolytic and antidepressant potential of Saurauia roxburghii Wall. Leaves: Supported by in vitro, in vivo, and in silico approaches - Md. Asibur Rahman; Kishore Kumar Sarkar; Md. Aktaruzzaman; Trina Mitra; Md. Takim Sarker; Md. Ahsan Abid; Kishor Mazumder; Apurba Kumar Barman; Nazim Uddin Molla; A.S.M. Monjur Al Hossain (Phytomedicine Plus)
Saurauia roxburghii, locally known as Dalup, has been utilizing as a treatment for Asthma, Bronchitis, Central Nervous System (CNS) Depression, Eczema, Fever, Gout, Hepatitis B, Piles, and Ulcers by inhabitants from hill-tract of Bangladesh for many years. Blended scientific approaches were applied to evaluate the antioxidant and neuropharmacological activities of the methanol extract of Saurauia roxburghii Wall. Leaves (MSRL) followed by experimental and in silico analysis. Firstly, the qualitative phytochemical screening, acute toxicity study and antioxidant activity assays were conducted. Then elevated plus maze, hole board, hole cross, open field, forced swimming, and tail suspension tests for neuropharmacological potentials were also investigated. Finally, molecular docking and ADMET analysis were carried out based on the bioactive compounds identified by GC-MS profiling. MSRL exhibited moderate antioxidant activity with a substantial amount of antioxidant components in different in vitro assays. In the Elevated Plus Maze and Hole Board test, a higher dose of MSRL (400 mg/kg) exhibited a significant reduction in anxiety-like behavior evidenced by enhanced time spent and entries into open arms, and an increase in the number of head dips, respectively suggesting anxiolytic activity. Moreover, dose-dependent locomotor activity was observed by MSRL in both Open Field and Hole Cross tests. In terms of Forced Swimming and Tail Suspension tests, both doses (200 and 400 mg/kg) of MSRL significantly declined the immobile time of mice indicating antidepressant effects. Lastly, in molecular docking analysis, amongst the identified compounds in GC-MS analysis, 5-(piperidin-1-ylmethyl)-3-pyridin-3-yl-5,6-dihydro-4h-1,2,4-oxadiazine showed strongest binding affinity against all the targeted receptors (Potassium channels receptor, GABAA receptor, and human serotonin transporter) followed by satisfactory ADMET profiling. So, S. roxburghii might have the potential to be used as a prominent source of novel therapeutics for anxiety and depression justifying the traditional usage.